2021
DOI: 10.1111/jcmm.16416
|View full text |Cite
|
Sign up to set email alerts
|

CLEC10A is a prognostic biomarker and correlated with clinical pathologic features and immune infiltrates in lung adenocarcinoma

Abstract: CLEC10A, (C‐type lectin domain family 10, member A), as the member of C‐type lectin receptors (CLRs), plays a vital role in modulating innate immunity and adaptive immunity and has shown great potential as an immunotherapy target for cancers. However, there is no functional research of CLEC10A in prognostic risk, immunotherapy or any other treatment of lung adenocarcinoma (LUAD). We performed bioinformatics analysis on LUAD data downloaded from TCGA (The Cancer Genome Atlas) and GEO (Gene Expression Omnibus), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 38 publications
1
16
0
Order By: Relevance
“…Lower CLEC10A expression was found to be associated with poorer prognosis. Some similar findings were reported in lung carcinoma, in a bioinformatics analysis on LUAD data downloaded from TCGA and Gene Expression Omnibus (12). Therefore, CLEC10A may be applied as a potentially powerful prognostic biomarker in BC clinical management.…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…Lower CLEC10A expression was found to be associated with poorer prognosis. Some similar findings were reported in lung carcinoma, in a bioinformatics analysis on LUAD data downloaded from TCGA and Gene Expression Omnibus (12). Therefore, CLEC10A may be applied as a potentially powerful prognostic biomarker in BC clinical management.…”
Section: Discussionsupporting
confidence: 74%
“…The ability of CLEC10A in promoting the antitumor activity of immune cells has been garnering attention (10,11), where it was proposed to be a target for cancer immunotherapy (8). Lower expression levels of CLEC10A in lung cancer have been reported to be associated with poorer clinical prognosis (12). Furthermore, a previous study based on artificial intelligence algorithms revealed that CLEC10A can be applied as prognostic biomarkers for BC (13).…”
Section: Clec10a Can Serve As a Potential Therapeutic Target And Its ...mentioning
confidence: 99%
“…To further explore the interactions between immune system and LOX family members that are associated with poor prognosis, the TISIDB database (http://cis.hku.hk/TISIDB) was used. TISIDB is a web portal for analyzing immune system and tumor interaction, including nearly one thousand reported immunerelated anti-tumor genes, etc., and immunological data gathered from seven public databases (129)(130)(131). Here, TISIDB was used for exploring the immunomodulators associated with LOX family members in LC.…”
Section: Immune Cell Infiltration Of Lox Family Members In Lcmentioning
confidence: 99%
“…Lung cancer is divided into small cell lung cancer and non-small cell lung cancer (NSCLC). Lung adenocarcinoma (LUAD) is the largest subgroup of NSCLC [2,3]. Despite improvements in systemic treatments for patients, the 5-year survival rate of LUAD patients is 15% [4].…”
Section: Introductionmentioning
confidence: 99%